Dimensi Misioner Gereja Dalam Masyarakat Plural: Mendalami Pergulatan Teologis Gereja Katolik Indonesia - Mariyanto, Vinsensius F. (Perspektif, 2015)
As a plural and multicultural society, a visionary and ideal state, Indonesia has been struggling to organise its diverse constellations of ethnic, religion, race, and group for the one, just, and peaceful society. Unfortunately, conflicts and violence among the people have come up from time to time; in particular, the writer mentions the happenings around the end of the New Era (Orde Baru) and the emerging era of Reformation. Within this very challenging context that the Church has been called to actualise her mission. How can the Church of Indonesia present her message meaningfully and work out fruitfully for the betterment of the society? How can the Church closely collaborate with people of other faiths and those of good will? The article tries to highlight an analysis with regard to the real mission context in the country and offer some theological insights that the Church could put into practice. Under the theological guidance of missio Dei for the Reign of God, the Church of Indonesia is undoubtedly struggling to energize herself to be a community of believers in dialogue with its context, namely the diverse people in the multicultural society in all its dynamic.